Pesticidas e abelhas - Amaro, Pedro (2012)
After the analysis of the criterion of toxicological classification (TC) of pesticides to honeybees and of the evolution of TC and of legislation related to the theme, in Portugal, it is demonstrated how the absence of rigor of the Portuguese Pesticide Regulation Authority (AFN) and of the pesticides suppliers contribute to the very high probability of mortality of honeybees by pesticides and finally are presented proposals for the optimization of perspectives to modify the actual situation